Pendelbereitschaft von Arbeitnehmern in Deutschland - Eckey, Hans-Friedrich; Kosfeld, Reinhold; Türck, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
An analysis of the commuter behaviour is an important question because of the high unemployment rate in many German regions. However, there are no actual investigations for the whole country. We use data of the Federal Employment Office (Bundesagentur für Arbeit), which include all national insurance contributors, to estimate gravity models. These calculations show the willingness to travel from home to work for all employed persons as well as for sociodemographic subgroups. It can be stated that men are more prepared to commute than women if the distance is increasing, that Germans are more willing to commute than foreigners and that workers have a greater commuting resistance than other employees. A local analysis shows that the influence of distance on commuting is higher in East German regions than in West Germany. One reason for that result may be the lower wages in East Germany. Employees accept longer driving times to work in economically prosperous regions in West Germany.